Pengaruh Media Pembelajaran Interaktif Menggunakan Visual Basic pada Aplikasi Excel Spreadsheet untuk Mengurangi Miskonsepsi dalam Pembelajaran Fisika - Roza Zulfira; Abdul Halim; Ibnu Khaldun; Elmi Mahzum; Muhammad Nazar; Elisa Kasli (Postgraduate, University of Mataram, 2024)
Misconceptions in physics learning are often caused by students’ preconceptions that are not in accordance with the actual physics theory. The use of interactive digital technology-based learning media makes it easier for students to understands physics concepts. This research aims to apply interactive learning media based on Visual Basic for Application (VBA) excel spreadsheets to remediate misconceptions in traveling wave material. The research method is a pre-experimental design, with one group for pretest and posttest. A total of 21 samples were selected using purposive sampling technique. Data collection was carried out twice, namely during the pretest and posttest using a five-tier multiple choice diagnostic test with 10 questions. The results of the misconception remediation analysis showed a decrease in misconceptions from 28.5% to 11.3% with an average N-Gain score (-0.31). This means that there was a decrease in the percentage of misconceptions before and after treatment. This data is also supported by the results of the paired sample t-test analysis, namely 0.000 < 0.5, which means that the use of interactive learning media based on Visual Basic for Application (VBA) Excel spreadsheets has a significant effect on remediating students' misconceptions about traveling wave material. This interactive learning media is expected to be an alternative for teachers in remediating misconceptions in learning physics.